Hydrophobic low glass transition temperature oligomers containing chain transfer agents
Through the use of hydrophobic pool or low molecular measurement polymers in the coherent composition, the problem of liquidity of the color of the color of the color of the color of the color of the color of the color of the color is solved, and the liquidity of the color agent and the quality of the paint thin film are realized.
Patent Information
- Application Number
- CN202380046495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is prone to clogging problems when maintaining colorant tanks, which affects the distribution of colorant and the accuracy of paint color. Conventional hydrophilic moisturizers can lead to water sensitivity of paint films, resulting in undesirable surfactant leaching. .
Use hydrophobic oligomers or low molecular weight polymers as humectants, maintain low molecular weight through a large amount of chain transfer agents, and add them to the colorant composition to maintain the fluidity of the colorant and prevent clogging, while not Affects the quality of paint or dye films.
Effectively reduce the tip of the color tank, maintain the liquidity of the color, and will not adversely affect the quality of the paint or dye film, and improve the accuracy of the paint color and the performance of the film.
Smart Images

Figure BDA0005182784050000061 
Figure BDA0005182784050000062 
Figure BDA0005182784050000071
Abstract
Description
[0001] Cross-references to related patent applications
[0002] This patent application is a continuation-in-part of International Patent Application No. PCT / US2020 / 063918, filed on December 9, 2020, under 35 U.S.C. §120, which claims priority under 35 U.S.C. §119(e) to U.S. Provisional Patent Application No. 62 / 954,906, filed on December 30, 2019. The parent patent application is incorporated by reference in its entirety. Technical Field
[0003] The present invention relates to hydrophobic oligomers which, when added to colorant compositions, can reduce clogging events at the tips of colorant cans. The present invention also relates to hydrophobic oligomers which can be added to paint and dye compositions as open time additives and which do not adversely affect the quality of the paint or dye film. Background Art
[0004] Most tintable base paints produced in factories are shipped to paint stores without colorants. When consumers purchase paint and select paint colors, multiple colorant compositions (referred to as chromogens) are added to and mixed with the tintable paint to obtain the final paint color. U.S. Pat. No. 9,994,722, co-owned by Sheerin et al., describes the process of tinting or coloring tintable base paints using colorant compositions at the point of sale, and is incorporated herein by reference in its entirety. Many tintable base paints contain opacifying pigments, except for dark or 4-based tintable paints containing little or no opacifying pigments, as discussed in Sheerin et al. U.S. Pat. Nos. 7,402,627, 7,750,074, 9,139,676, and 9,815,961, co-owned by Yang et al., describe high-end water-based colorants, and are incorporated herein by reference in their entirety.
[0005] The colorant composition is typically stored in a can for dispensing into a tintable base paint. One disadvantage of maintaining a colorant can is that the dispensing tip of the can must be cleaned periodically because the colorant can dry and partially or completely clog the can tip. A completely clogged can tip prevents dispensing of the colorant, while a partially clogged can tip will prevent dispensing of the correct amount of each colorant to mix the correct paint color.
[0006] One conventional solution is to add humectants, e.g., hydrophilic additives, such as polyethylene glycol, such as PEG 400, to the colorant to maintain fluidity of the colorant composition within the colorant can. While retaining moisture, such hydrophilic additives can cause water sensitivity of the dried paint film, thereby causing undesirable leaching of surfactants, which can leave unsightly but washable streaks on the paint film.
[0007] Therefore, there remains a need to maintain the tip of the colorant can open to allow unobstructed dispensing of the colorant without negatively affecting the properties of the paint film. Summary of the invention
[0008] One embodiment of the present invention relates to a novel humectant, and unlike conventional humectants, the humectant of the present invention is hydrophobic and is preferably an oligomer or a low molecular weight polymer. Preferably, the humectant of the present invention also has a low glass transition temperature (Tg) so that the humectant of the present invention remains in a liquid or viscous phase within a temperature range associated with applying paints and dyes to walls or floors and associated with drying paint and dye films. More preferably, the humectant of the present invention also has an optimal viscosity or flow viscosity range to assist the colorant in flowing through a dispenser.
[0009] In another embodiment, the humectants of the present invention utilize relatively large amounts of chain transfer agents to maintain low molecular weight. In another embodiment, the amount of chain transfer agent used is significantly higher than the levels used or experimented with to date in polymerization for controlling molecular weight. Suitable chain transfer agents include, but are not limited to, monofunctional mercaptans such as monothiol or compounds with sulfur-hydrogen (SH) functional groups, such as preferred isooctyl 3-mercaptopropionate (iOMP) and n-dodecyl mercaptan (n-DDM), as well as other compounds described below.
[0010] One embodiment of the present invention relates to an additive for a paint or dye composition or for a colorant composition. The additive is polymerized from at least one acrylate monomer and a chain transfer agent. The additive preferably has a weight average molecular weight (Mw) of about 2,000 Daltons to about 5,000 Daltons, preferably about 2,500 Daltons to about 4,000 Daltons. The chain transfer agent preferably contains a hydrogen-sulfur (HS) functional group and is present in an amount of about 8 to about 20 parts per hundred monomers (phr), preferably about 9 to about 17 phr, more preferably about 9.5 to about 15 phr. The glass transition temperature of the additive ranges from about -50°C to about -10°C, preferably about -40°C to about -20°C. The additive is hydrophobic. The additive is preferably added to the colorant composition. The colorant composition comprises a coloring pigment and an optional opacifying pigment.
[0011] In one embodiment, the additive accounts for about 3% to about 8% by weight of the colorant composition. Alternatively, the additive accounts for about 3.5% to about 7% by weight, or about 4.0% to about 6% by weight, or about 3% to about 5% by weight of the colorant composition. In the determination of the weight percentages, the additive and the colorant composition include solids, water, and liquids.
[0012] In another embodiment, a hydrophilic moisturizer is also added to the colorant composition, and the additive accounts for about 0.1% to about 4% by weight of the colorant composition. Alternatively, the additive accounts for about 0.2% to about 3% by weight or about 0.3% to about 2.5% by weight of the colorant composition. In the determination of the weight percentage, the additive and the colorant composition include solids, water and liquids.
[0013] Preferably, the at least one acrylate monomer comprises a major acrylate monomer, and the major acrylate monomer accounts for at least 50% by weight of all monomers, preferably at least 60% by weight, preferably at least 70% by weight, preferably at least 75% by weight, and the at least one acrylate monomer preferably has a solubility in water at 20°C to 30°C of less than 5g / l, preferably less than 4g / l or preferably less than 3g / l. In one embodiment, the major monomer is butyl acrylate (BA). In another embodiment, the major monomer is 2-ethylhexyl acrylate (2-EHA). In another embodiment, the at least one acrylate monomer comprises at least BA and 2-EHA.
[0014] Another embodiment of the present invention relates to an additive for a paint or dye composition or for a colorant composition, which is polymerized from at least one acrylate monomer and a chain transfer agent. The additive has a weight average molecular weight (Mw) of about 2,000 Daltons to about 5,000 Daltons. The chain transfer agent contains a hydrogen-sulfur (HS) functional group and is present in about 4 to about 20 parts per hundred monomers (phr). The glass transition temperature of the additive ranges from about -50°C to about -10°C, and the additive is hydrophobic. When the viscosity values are averaged at the same shear rate, the additive has a viscosity of about 1.0 Pa·s to about 20 Pa·s, or when the viscosity values are averaged at various shear rates, the viscosity is about 14 Pa·s to about 36 Pa·s.
[0015] The additive may be polymerized from at least 95% by weight of one or more acrylate monomers or from all acrylate monomers. The at least one acrylate monomer is preferably butyl acrylate (BA) or 2-ethylhexyl acrylate (2-EHA).
[0016] In a preferred variant, the additive is polymerized as an acrylic monomer.
[0017] In another embodiment, the additive is added to a colorant composition, which has a coloring pigment and an optional opacifying pigment. The additive is added to the colorant composition in the range of about 3 % by weight to about 8 % by weight, preferably about 3.5 % by weight to about 7 % by weight, preferably about 4 % by weight to about 6 % by weight, preferably about 3 % by weight to about 5 % by weight. In a variant, the colorant composition comprises a hydrophilic moisturizer, a pigment and an additive of the present invention. The additive is added to the colorant composition in the range of about 0.1 % by weight to about 4 % by weight, preferably about 0.2 % by weight to about 3 % by weight, preferably about 0.3 % by weight to about 2.5 % by weight. In the determination of the weight percentage, the additive and the colorant composition include solid, water and liquid.
[0018] The chain transfer agent may be present at about 6 phr to about 17 phr, or about 9 phr to about 15 phr, or about 5 phr to about 11 phr.
[0019] When the viscosity values are averaged at the same shear rate, the viscosity of the additive may be about 3.0 Pa·s to about 16 Pa·s, or about 5 Pa·s to about 12 Pa·s. When the viscosity values are averaged at various shear rates, the viscosity may be about 15 Pa·s to about 20 Pa·s.
[0020] Alternatively, the additive can be added directly to the paint or dye composition. The paint or dye composition further comprises a film-forming resin and an optional opacifying pigment. As used herein, the effect of the opacifying pigment is to hide the surface covered by the paint or dye composition, and comprises titanium dioxide. As used herein, the opacifying pigment is different from the coloring pigment that the toning paint or dye composition is toned or painted. Titanium dioxide pigment also can be used in the colorant composition to give whiteness.
[0021] These and other objects of the present invention are achieved by the following claims, and various embodiments and aspects of the present invention are described in the following detailed description and claims.
[0022] Specific implementation methods of the preferred embodiment
[0023] According to one aspect of the present invention, the inventors have discovered a hydrophobic oligomer having a Tg below about -10°C and above about -50°C made with a large amount of chain transfer agent, from about 8 to about 20 phr of the total monomer weight (parts per hundred monomers per rubber), preferably iOMP or n-DDM, such that the hydrophobic oligomer remains in a liquid or viscous phase over the relevant temperature range of paints and colorants. The weight average molecular weight (Mw) of the oligomer of the present invention is preferably from about 2,000 Daltons to about 5,000 Daltons.
[0024] Preferably, the amount of chain transfer agent may be in the range of about 9 to about 17 phr and preferably about 9.5 to about 15 phr. Preferably, the weight average molecular weight of the hydrophobic oligomers of the present invention may be in the range of about 2,500 Daltons to about 4,000 Daltons. Preferably, the Tg of the hydrophobic oligomers of the present invention may be in the range of about -50°C to about -10°C or preferably about -40°C to about -20°C. Preferably, the hydrophobicity of the oligomers of the present invention is explained by the solubility of the monomer in water, as discussed below.
[0025] The hydrophobic oligomers of the present invention are preferably polymerized from mainly acrylic monomers and more preferably from at least one "mainly acrylic monomer", and more preferably polymerized by emulsion polymerization, the at least one "mainly acrylic monomer" such as butyl acrylate monomer (BA) or 2-ethylhexyl acrylate (2-EHA), which also has low solubility in water to ensure the hydrophobicity of the oligomer. The main acrylic monomer used herein accounts for at least about 50% by weight of the total monomers, preferably at least about 60% by weight, or at least about 70% by weight or at least about 75% by weight.
[0026] Other suitable low Tg and low solubility acrylic monomers include, but are not limited to, 2-ethoxyethyl acrylate (Tg = -50°C), 2-methoxyethyl acrylate (Tg = -50°C), and octadecyl methacrylate (Tg = -100°C; solubility 1 μg / l at 25°C).
[0027] As long as the resulting oligomer is hydrophobic and has a Tg within the range, "other acrylic monomers" and "other monomers" may also be included in the hydrophobic oligomers of the present invention. Suitable other acrylic monomers may include methyl methacrylate (MMA) and methacrylic acid (MAA). Suitable other monomers may include vinyl or styrene. Latexes made primarily of acrylic monomers are preferred for the present invention, although other non-acrylic monomers are included within the scope of the present invention.
[0028] Any acrylic monomer can be used as other acrylic monomers. Any (meth) acrylic monomer can be used in the present invention. Suitable (meth) acrylic monomers include, but are not limited to, methyl (meth) acrylate, ethyl (meth) acrylate, butyl (meth) acrylate, isooctyl (meth) acrylate, lauryl (meth) acrylate, 2-ethylhexyl (meth) acrylate, stearyl (meth) acrylate, isobornyl (meth) acrylate, methoxyethyl (meth) acrylate, 2-ethoxyethyl (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, dimethylaminoethyl (meth) acrylate, diethylaminoethyl (meth) acrylate, dimethylaminopropyl (meth) acrylamide, alkyl (meth) acrylic acid such as methyl (meth) acrylic acid, (meth) acrylic acid, wet bonding monomers such as N-(2-methacryl) acrylate The preferred monomers include divinylbenzene, diacrylates for crosslinking functions, acrylic acid, ionic acrylates, alkyl acrylic acid, ionic alkyl acrylates, halogenated acrylic acid, ionic halogenated acrylates, acrylamide, alkyl acrylamide, monoalkyl acrylamide, monoalkyl alkyl acrylamide, alkyl acrylate, alkyl acrylate, acrylonitrile, alkyl acrylonitrile, dialkyl acrylamide, dialkyl alkyl acrylamide, hydroxyalkyl acrylate, hydroxyalkyl alkyl acrylate, only partially esterified acrylate of alkylene glycol, only partially esterified acrylate of non-polymeric polyols such as glycerol, only partially esterified acrylate of polymeric polyols, itaconic acid, itaconic acid monoesters and diesters, and combinations thereof. Preferred alkyl (meth)acrylate monomers are methyl methacrylate and butyl acrylate.
[0029] Preferred other monomers or other non-acrylic monomers include monomers containing aromatic groups, such as styrene and α-methylstyrene. Other suitable monomers containing aromatic groups include, but are not limited to, 2,4-diphenyl-4-methyl-1-pentene, 2,4-dimethylstyrene, 2,4,6-trimethylstyrene, 2,3,4,5,6-pentafluorostyrene, (vinylbenzyl)trimethylammonium chloride, 2,6-dichlorostyrene, 2-fluorostyrene, 2-isopropenylaniline, 3 (trifluoromethyl)styrene, 3-fluorostyrene, α-methylstyrene, 3-vinylbenzoic acid, 4-vinylbenzyl chloride, α-bromostyrene, 9-vinylanthracene, and combinations thereof.
[0030] Preferred other monomers containing primary amide groups are (meth) acrylamide. Suitable monomers containing amide groups include, but are not limited to, N-vinylformamide or any vinylamide, N,N-dimethyl (meth) acrylamide, N-(1,1-dimethyl-3-oxobutyl) (meth) acrylamide, N-(hydroxymethyl) (meth) acrylamide, N-(3-methoxypropyl) (meth) acrylamide, N-(butoxymethyl) (meth) acrylamide, N-(isobutoxymethyl) acryloyl (meth) acrylamide, N-[tris (hydroxymethyl) methyl] acryloyl (meth) acrylamide, 7-[4-(trifluoromethyl) coumarin] (meth) acrylamide, 3-(3-fluorophenyl)-2-acrylamide, 3-(4-methylphenyl) (meth) acrylamide, N-(tert-butyl) (meth) acrylamide, and combinations thereof. These monomers can be polymerized with the acrylic monomers listed above. The general formula of vinyl (form) amide is:
[0031]
[0032] And the general formula of (meth)acrylamide is:
[0033]
[0034] Where R 1 and R 2 Can be -H, -CH 3 、-CH 2 CH 3 and other substituted organic functional groups, and R 3 It can be -H, alkyl or aryl.
[0035] In one embodiment, the other monomers may also include vinyl monomers. Monomers of this type suitable for use in accordance with the present invention include any monomer having a vinyl functional group (ie, -CH=CH 2 Preferably, the vinyl monomer is selected from the group consisting of vinyl esters, vinyl aromatic hydrocarbons, vinyl aliphatic hydrocarbons, vinyl alkyl ethers and mixtures thereof.
[0036] Suitable vinyl monomers include vinyl esters such as, for example, vinyl acetate (VA), vinyl propionate, vinyl laurate, vinyl pivalate, vinyl nonanoate, vinyl decanoate, vinyl neodecanoate, vinyl butyrate, vinyl hexanoate, vinyl benzoate, vinyl isopropyl acetate and similar vinyl esters; nitrile monomers such as (meth) acrylonitrile and the like; vinyl aromatics such as, for example, styrene, methyl styrene and similar lower alkyl styrenes, chlorostyrene, vinyl toluene, vinyl naphthalene and divinylbenzene; vinyl aliphatic hydrocarbon monomers such as, for example, vinyl chloride and vinylidene chloride and alpha olefins such as, for example, ethylene, propylene, isobutylene, and conjugated dienes such as 1,3-butadiene, methyl-2-butadiene, 1,3-pentylene, 2,3-dimethylbutadiene, isoprene, cyclohexene, cyclopentadiene and dicyclopentadiene; and vinyl alkyl ethers such as, for example, methyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether and isobutyl vinyl ether.
[0037] Polymerizable diols such as methoxy polyethylene glycol (MPEG) or polypropylene glycol methyl ether can also be polymerized with other monomers. A preferred polymerizable diol is MPEG 750, which has 17 ethylene oxide (EO) side chain units. MPEG with different EO chain lengths can also be used, MPEG 250, MPEG 350, MPEG 500, MPEG 1000, MPEG 3000, etc. The diols are polymerized to prevent the hydrophilic PEG compound from leaching out of the paint film (e.g., when the film is wetted).
[0038] Suitable chain transfer agents include, but are not limited to, monofunctional mercaptans such as monothiol or compounds having sulfur-hydrogen (SH) functional groups. A preferred chain transfer agent is isooctyl 3-mercaptopropionate (iOMP) disclosed in co-owned U.S. Patent No. 7,642,314 to Gharapetian et al. The preferred iOMP (C 11 H 22 O 2 S) Chain transfer agent has the following structure:
[0039]
[0040] Other suitable mercaptan chain transfer agents include, but are not limited to, n-dodecyl mercaptan (n-DDM), tert-dodecyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, sec-octyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, n-hexyl mercaptan, n-pentyl mercaptan, n-butyl mercaptan, tert-butyl mercaptan, n-butyl 3-mercaptopropionate (BMP), methyl 3-mercaptopropionate, etc., disclosed in U.S. Pat. Nos. 4,593,081 and 7,256,226, and mixtures thereof. The '081 patent further discloses other non-mercaptan chain transfer agents. All patent references cited in this paragraph are incorporated herein by reference in their entirety. n-DDM is another preferred chain transfer agent.
[0041]
[0042] Additives including surfactants, initiators, chaser solutions, biocides, rheology modifiers, etc. may be added during the polymerization process.
[0043] Examples of surfactants useful in the polymerization process may include, but are not limited to, nonionic and / or anionic surfactants such as ammonium nonylphenol polyether-4 sulfate, nonylphenol (10) ethoxylate, nonylphenol (~10 mol%) ethoxylate, nonylphenol (~40 mol%) ethoxylate, octylphenol (~40 mol%) ethoxylate, octylphenol (9-10) ethoxylate, sodium dodecyl sulfate, sodium tetradecyl sulfate, sodium hexadecyl sulfate, polyether phosphate esters, alcohol ethoxylate phosphate esters, Triton 60 ... TM Those compounds sold under the trade name Rhodapon TM Those compounds sold under the trade name Rhodapex TM Those sold under the trade name Rhodacal TM Those compounds sold under the trade name Rhodafac TM Those compounds sold under the same, etc., and combinations thereof.
[0044] Examples of initiators and chaser solutions useful in the polymerization process may include, but are not limited to, ammonium persulfate, sodium persulfate (SPS), azo initiators such as azoisobutyronitrile, redox systems such as sodium hydroxymethanesulfinate (sodium formaldehyde sulfoxylate; reducing agent) and tert-butyl hydroperoxide (oxidizing agent), and the like, and combinations thereof, typically in aqueous solution. Either or both of these components may optionally contain additional surfactants and / or pH adjusters if desired to stabilize the emulsion.
[0045] Examples of pH adjusters useful in the polymerization process may include, but are not limited to, ammonium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, ammonia, amines such as trimethylamine, triethylamine, dimethylaminoethanol, diethylaminoethanol, AMP-95, and the like, and combinations thereof. In some cases, compounds that qualify as pH adjusters may be added for purposes other than adjusting pH, such as emulsion stabilization, and are still characterized herein as pH adjusters.
[0046] Preferably, the latex emulsion polymer is chased with a redox (reducing agent and oxidizing agent) pair to reduce odor and neutralize unreacted monomer without requiring a lengthy or time consuming stripping step or the need for additional stripping equipment.
[0047] Suitable oxidizing agents include, but are not limited to, water-soluble hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, hydrogen peroxide, sodium peroxide, potassium peroxide, sodium perborate, potassium persulfate, sodium persulfate, ammonium persulfate, persulfate and its salts, perphosphoric acid and its salts, potassium permanganate, and ammonium or alkali metal salts of peroxodisulfate. A preferred oxidizing agent is tert-butyl hydroperoxide (tBHP).
[0048] Suitable reducing agents include, but are not limited to, sodium formaldehyde sulfoxylate (SFS), ascorbic acid, isoascorbic acid, organic compounds containing thiol or disulfide groups, reducing inorganic base salts and ammonium salts of sulfuric acid such as sodium sulfite, pyrosulfite, thiosulfate, bisulfite, sulfide, hydrosulfide or dithionite, formadinesulfinic acid, hydroxymethanesulfonic acid, acetone bisulfite, amines such as ethanolamine, glycolic acid, glyoxylic acid hydrate, lactic acid, glyceric acid, malic acid and tartaric acid. A preferred reducing agent is SFS without formaldehyde.
[0049] The following non-limiting Example 1 illustrates the emulsion polymerization of the hydrophobic oligomeric moisturizer of the present invention. A monomer pre-emulsion is prepared while the deionized water (DI) in the reactor is heated to 80°C. 36 grams of seed and the first initiator are added to a reactor at 80°C and maintained for 15 minutes. The monomer pre-emulsion feed is added to the reactor, and then the second initiator or delayed initiator is added to the reactor over a period of 3 hours and then maintained for 30 minutes. The contents of the reactor are cooled to 55°C and then chased within 30 minutes. Thereafter, the contents of the reactor are cooled to 35°C and then a pH adjuster (ammonia) and a biocide are added. In this Example 1, the latex particles have a calculated Tg of -27°C.
[0050] The overall Tg of a copolymer calculated by Fox's equation includes the individual Tgs of the various monomers copolymerized as follows:
[0051] 1 / Tgagg =Wf 1 / Tg 1 +Wf 2 / Tg 2 +Wf x / Tg x ,
[0052] Where Tg agg is the overall Tg of the copolymer,
[0053] W x is the weight fraction of each monomer x,
[0054] Tg x is the Tg of a polymer prepared from a single monomer x, and
[0055] x is the number of monomers in the copolymer.
[0056] Tg can also be measured by differential scanning calorimetry (DSC) techniques. Unless otherwise indicated, Tg used herein is calculated by Fox's equation; all percentages are based on weight or wt%; and all molecular weights are weight average molecular weight (Mw).
[0057] Example 1 .
[0058]
[0059]
[0060] The total monomer weight is 528 grams. Therefore, 73.2 grams of iOMP is about 14 phr (73.2÷528) (parts per hundred monomers per rubber).
[0061] Several additional examples of hydrophobic oligomers of the present invention were prepared using the emulsion polymerization technique of Example 1. The results are summarized below.
[0062]
[0063] As shown in Examples 1-6, higher levels of chain transfer agent (e.g., 14 phr) result in lower molecular weight (as expected) and lower viscosity. Due to the low glass transition temperature, the hydrophobic oligomers are in a liquid or viscous stage at room temperature and at a relevant temperature range for indoor and outdoor waterborne paint compositions and dried paint films (e.g., about 10°C (50°F) to about 50°C (122°F)). Their viscosities are measured and reported. Therefore, the inventors of the present invention believe that the hydrophobic oligomers do not form a film and that in the paint film, the hydrophobic oligomers are bound to the latex particles by hydrophobic interactions. The hydrophobic oligomers of the present invention are compatible with pigments and other particles in the colorant composition.
[0064] Compared to Example 6 which contains a typical amount of MAA, Examples 1-4 contain higher amounts of MAA monomers, and the MAA monomers are hydrophilic. Examples 3 and 5 also contain small amounts of hydrophilic MPEG monomers. Without being limited to any particular theory, the inventors of the present invention believe that a certain hydrophilicity is required in order to achieve better stability and bonding in the colorant composition and in the paint composition. The oligomer latex is also successful as an anti-tip drying additive because the overall oligomer is still essentially hydrophobic and fluid, and can be used in place of humectants in the colorant formulation due to its fluid properties. Oligomers with lower hydrophilic monomers are preferred due to better resistance to surfactant leaching. In addition, Examples 1 and 4 have similar monomer content and Example 4 utilizes more initiator. In addition, without being limited to any particular theory, the inventors of the present invention believe that hydrophobic soft polymers or oligomers (with low Tg) provide the possibility of preparing soft and flowing polymers or oligomers and the ability to keep the oligomer flowing in the absence of water.
[0065] The monomer and chain transfer agent content of Example 1 was repeated, i.e., 14 phr, and contained 80% BA, 15% MMA, and 5% MAA, as shown below. Examples 4, 7, 8, 9, and 10 utilized the same formulation, except that Examples 9 and 10 used less initiator, which was similar to Example 1. The viscosity of Example 1 was similar to that of Examples 9 and 10. As shown below, there was no significant difference in molecular weight or viscosity, and no significant difference in anti-tip drying performance. Therefore, preferably, lower amounts of initiator are preferred.
[0066] Example Molecular weight (Dalton) Viscosity (Pa·s) 4 2650 15.88 7 2422 15.66 8 2465 15.73 9 2641 16.43 10 2654 15.86
[0067] The embodiment containing 14phr of iOMP has substantially similar performance, and the results are repeatable, as is the embodiment containing 10phr of iOMP. The embodiment of the present invention containing 14phr of iOMP has a significantly lower molecular weight than the embodiment containing 10phr. Due to their similar monomer composition, viscosity and molecular weight, embodiments 1, 4 and 7-10 are considered as a group during the performance test. Molecular weight and viscosity results suggest that the effect of high-level chain transfer agent IOMP on the molecular weight of oligomers may dominate the effect of changes in initiator concentration.
[0068] In Example 11, a higher amount of CTA (e.g., 20 phr) was included in the polymerization of the monomers to show that higher CTA content is feasible and allows even lower molecular weight of the oligomers. Example 12 has 14 phr of CTA and is compared to Example 11 to measure molecular weight, as discussed below. The monomers polymerized included 80 wt% BA, 15 wt% MMA, and 5 wt% MAA.
[0069] The CTA is an iOMP.
[0070] Example CTA Molecular weight (Dalton) 11 20phr 2,081 12 14phr 2,982
[0071] The molecular weight of the higher CTA in Example 11 is within the preferred range of the molecular weight of the oligomers of the present invention described above.
[0072] The molecular weight of the hydrophobic oligomers of the present invention was determined by a GPC instrument of water equipped with a refractive index and UV detector using a THF mobile phase, which is a weight average molecular weight. After the water had evaporated leaving a substantially clear or transparent fluid at room temperature, the viscosity was measured on a dried sample of the examples. The viscosity of Examples 1-10 was measured using an Anton Paar modular compact rheometer MCR 302, which measures the viscosity as the average value of the measurements at various shear rates.
[0073] As used herein, solubility is an indicator of the degree of hydrophilicity and hydrophobicity. Lower solubility indicates stronger hydrophobicity, and higher solubility indicates stronger hydrophilicity. It is known that BA, EA, and dodecyl methacrylate have low Tg and are hydrophobic. See "Mechanical Properties of Hydrophilic Copolymers of 2-Hydroxyethyl Methacrylate with Ethyl Acrylate, N-Butyl Acrylate, and Dodecyl Methacrylate," J Biomed Mater Res. 1983 September; 17(5): 757-67 (available at www.ncbi.nlm.nih.gov / pubmed / 6619175).
[0074] Preferably the primary acrylic monomer (e.g., BA or 2-EHA) should have a low solubility, preferably less than about 5 g / l, more preferably less than about 4 g / l, or less than about 3 g / l at 20°C to 30°C. There does not appear to be a consensus in the scientific literature on the temperature at which solubility is measured. Therefore, the present invention contemplates the reported solubility values, which are summarized below along with the calculated Tg values. Note that the resulting oligomer is preferably hydrophobic, more hydrophobic than either monomer.
[0075]
[0076]
[0077] (DMA is dodecyl methacrylate, also known as lauryl methacrylate, preferably long chain (C 12 and C 13 ), and AA is acrylic acid). Solubility information is obtained from https: / / www.ncbi.nlm.nih.gov / pccompound and https: / / echa.europa.eu / . Tg information is obtained from https: / / www3.nd.edu / ~hgao / thermal_transitions_of_homopolymers.pdf, or http: / / www.wernerblank.com / equat / Fox_equation15.htm. The freezing point of iOMP is about -10°C (see https: / / www.chemicalbook.com / ProductChemicalPropertiesCB2757359_EN.htm).
[0078] A set of experiments were conducted using aqueous colorant compositions described in the above-mentioned Yang et al. co-owned U.S. Patent Nos. 7,402,627, 7,750,074, 9,139,676 and 9,815,961. The experiments were conducted with inorganic colorants (e.g., red oxide colorants) and organic colorants (e.g., carbon black colorants and phthalocyanine blue). These colorant compositions had polyethylene glycol (PEG) added thereto as a hydrophilic humectant. PEG is liquid in the relevant temperature range and is very soluble in water (256 g / l at 25° C.). PEG was replaced by the hydrophobic humectant of the present invention in Examples 2-6 in a weight ratio of 1:1. Red oxide, carbon black and phthalocyanine blue colorant compositions were tested. About 20% by weight of the hydrophobic oligomer of the present invention was added to the red oxide and phthalocyanine blue colorant compositions, and about 10% by weight was added to the carbon black colorant composition. In these experiments, the hydrophobic oligomers of the present invention may be added at about 6% to about 30% by weight of the colorant composition, preferably about 8% to about 27.5% or about 9% to about 25% by weight.
[0079] The colorant composition used herein is not a paint or dye composition. The colorant composition is mixed into a tintable paint or dye composition at the point of sale to tone the paint and dye. The colorant composition may include a small amount of adhesive, and the adhesive is not enough to form a film or matrix that encapsulates the pigment contained in the colorant composition. The colorant composition contains a coloring pigment and may also contain an opacifying pigment, such as titanium dioxide, to impart whiteness.
[0080] Tip drying experiment. The effectiveness of the hydrophobic oligomers of the present invention as anti-tip drying agents was evaluated. The tips of pipettes with a capacity of 7 ml were cut to a diameter of about 3 mm to simulate the tips of the colorant jars on the color mixing machine. The colorant compositions were loaded into these pipettes and the pipettes were left to stand for a predetermined period of time, i.e., 16 hours in this experiment. After the predetermined period of time had passed, the colorant samples were dispensed from the cut ends of the pipettes. A rating system was designed to quantify the anti-tip drying effectiveness as follows:
[0081] Rating describe 0 Failure - Complete blockage 1 Maximum pressure 2 High pressure 3 Some pressure 4 Minimum pressure 5 No clogging
[0082] Ratings of 1 to 4 may include some angle assignments.
[0083]
[0084] The results show that the hydrophobic oligomers of the present invention consistently outperform conventional PEG hydrophilic moisturizers in terms of effectiveness in preventing tip drying.
[0085] Colorant drying experiment Another experiment was conducted to test the drying characteristics of the colorant composition on the substrate. A 10 mil (10 thousandths of an inch) drawdown of the colorant composition was performed on a white scrub card. At various time intervals, a line of sand was applied to the film. This process continued until the colorant composition was dry and the sand no longer adhered to the colorant.
[0086]
[0087] The results show that for the red oxide inorganic colorant, the hydrophobic oligomeric humectants of the present invention outperformed the PEG hydrophilic humectants by a significant amount of time.
[0088]
[0089]
[0090] The results show that the hydrophobic oligomer humectant of the present invention performs comparable to the PEG hydrophilic humectant when used with an organic colorant. The inventors of the present invention believe that the relatively small amount of the hydrophobic oligomer of the present invention used (10 wt % at 10 phr) does not sufficiently improve the open time compared to conventional hydrophilic PEG, and the carbon black organic colorant has smaller pigment particles, resulting in lower total solids in the colorant and requiring less humectant. On the other hand, the red oxide inorganic colorant has larger pigment particles, resulting in higher total solids in the colorant and requiring more humectant.
[0091] Can tip experiment at point of sale . The red oxide colorant composition was loaded into a point-of-sale manual rotary dispenser. PEG moisturizer and Inventive Example 4 (14 phr of CTA) were added to the colorant composition. After a predetermined inactivity time had passed, one fluid ounce of colorant was dispensed. After 48 hours of inactivity, the colorant composition containing the PEG moisturizer dried out and clogged the nozzle. After 48 hours of inactivity, the colorant composition containing Inventive Example 4 remained fluid and had not dried out, making it easy to clean the dispenser.
[0092] Color transfer experiment. Another set of experiments was conducted in which a commercial premium flat 3-base paint composition was tinted with the addition of a colorant composition containing a conventional PEG humectant and containing a hydrophobic oligomer of the present invention. Paint bases are discussed in co-owned patent number 9,994,722, which is incorporated herein by reference in its entirety. These experiments were conducted to compare the properties of the paint films, such as color transfer and surfactant leaching.
[0093] The color transfer (or color erasure) of paints tinted with red oxide colorants was measured on 3 mil drawdowns dried for 7 days. The test involves using a piece of water-soaked white felt, pressing it down and sliding it over the dry tinted paint film. The felt will rub off and absorb the color from the film. This test shows how hydrophilic or hydrophobic the paint film is. Hydrophilic films generally transfer more color than hydrophobic films. The difference between clean white felt and tinted felt is measured with a spectrophotometer, and the measurement result is ΔE or color change or color difference in CIE2000, the lower the value, the better the color transfer resistance.
[0094]
[0095] The results show that paints using colorants containing the hydrophobic oligomers of the present invention have better or comparable color rub-off resistance than paints using colorants containing conventional PEG humectants.
[0096] Surfactant leaching experiment.This test determines whether surfactants or other water-soluble materials can leach from the paint film to cause a spotty appearance or tan or brown spots on the paint film when certain environmental conditions are present. Surfactant leaching is a test to detect the extent of external water spots on the coating. The test method for surfactant leaching involves forming a 3 mil drawdown panel of each coating composition. These panels are then dried in air at about 72°F and 50% RH for about 24 hours. Each panel is then held so that the coating on the substrate is oriented vertically, and 3-5 drops of water are applied to the coated area. In addition, water is sprayed on the panels. The coatings are allowed to dry for 1 day and 7 days without changing the orientation of the panels. At 1 day and at 7 days, the presence or absence of visible stains on each panel is recorded for drops and sprays and rated from 1 to 5, where 1 represents the most obvious stain and 5 represents no visible stain. The maximum rating is 20.
[0097]
[0098]
[0099]
[0100]
[0101] The results show that surfactant leaching is comparable between conventional PEG humectants and the hydrophobic oligomers of the present invention used as humectants. This indicates that the hydrophobic oligomer additives of the present invention do not migrate to the surface of the paint film and do not promote leaching.
[0102] According to another aspect of the invention, the hydrophobic oligomer of the invention is added directly to the paint composition as an open time (OT) extension additive. A 7 mil primer is scraped over a scrubbed board. The primer is slightly toned to make the end point visible. After the board is dried overnight, a 3 mil flat topcoat is scraped over the dried primer film. The open time is measured using an AB3600 drying time recorder. The recorder measures with three probes at a time and runs multiple boards.
[0103] Opening hours experiment About 30 pounds of the hydrophobic oligomer of the present invention is added to 100 gallons of paint, which is equivalent to about 1.7 weight percent of the hydrophobic oligomer solids of the present invention to paint solids, or about 10 pounds of the hydrophobic oligomer solids of the present invention in 100 gallons of paint having about 52% solids. This ratio / percentage is also commonly used in commercial open time additives such as Preferably, as an open time agent, about 20 pounds to about 80 pounds of the hydrophobic oligomer of the present invention are added per 100 gallons of paint, more preferably about 30 pounds to about 50 pounds per 100 gallons. The preferred ratio for the open time experiment can be about 1.13 weight % to about 4.53 weight % of the hydrophobic oligomer solids of the present invention to the paint solids, preferably about 1.7 weight % to about 2.83 weight % of the hydrophobic oligomer solids of the present invention to the paint solids.
[0104] The following table lists paint samples without any OT additives, paint samples with the addition of Example 10 of the present invention, and paint samples with the addition of commercially available OT additives. of paint samples.
[0105]
[0106] The open time of the paint containing the hydrophobic oligomeric additive of the present invention was 1 minute better than the paint containing the commercial OT additive and 1.5 minutes better than the control paint.
[0107] Without being bound by any particular theory, the inventors of the present invention believe that the anti-tip drying properties and improved OT properties of the non-filming low Tg hydrophobic oligomers of the present invention can be attributed to the fact that the oligomers of the present invention are not volatile and remain in a liquid or flowable state within the relevant operating temperature range, thereby keeping the colorant composition softer for a longer time to provide better dispensability and OT. The inventors of the present invention also believe that the hydrophobicity and low Tg contribute to the open time and improved tip dispensability by keeping the oligomers of the present invention in a liquid or gel state. The inventors of the present invention also believe that the hydrophobicity and fluid properties of the oligomers of the present invention can control leachable substances in the paint film, such as non-reactive surfactants.
[0108] Additional examples of hydrophobic oligomeric additives of the present invention were prepared by utilizing a similar emulsion polymerization process as described in connection with Examples 1-12, unless otherwise indicated.
[0109]
[0110]
[0111] Examples 13-18 were run using less (meth)acrylate monomer (Example 13) or all acrylate monomer (Examples 14-18). Acrylic acid monomers were used instead of methacrylic acid monomers (Examples 13-18), and lower amounts of CTA were also tested (Examples 17-18). The oligomers in Examples 17-18 were liquid at room temperature (75°F). Reduction in acrylic acid monomers also reduced viscosity (Examples 17-18).
[0112] In Examples 1 and 13-18 shown in the table above, the viscosity values were measured using a Bohlin rheometer at a constant shear rate of 5 s -1 Up to 1,000s -1 The viscosity of Example 1 obtained using the average of 20 measurements made over a shear range of 1.30° and 1.60° respectively, is an average of 20 measurements made over a shear range of 1.30° and 1.60° respectively. The viscosity of Example 1 obtained using the average of 20 measurements under constant shear (6.31 Pa·s) and the viscosity of Example 1 obtained using the average of various shear rates (about 16 Pa·s in Examples 9 and 10 using the Anton Paar Modular Compact Rheometer MCR 302 model) illustrate a difference of about 9-10 Pa·s units or about 9.5 Pa·s units between the two viscosity measurement systems.
[0113] The inventors of the present invention have found that using acrylic acid monomers instead of methacrylic acid monomers reduces the viscosity of the oligomers, as shown in Examples 1 and 13. Using acrylate monomers instead of methacrylate monomers also reduces viscosity, as shown in Examples 1 and 14. Reducing the level of CTA also reduces viscosity, as shown in Examples 1 and 15, or does not significantly affect viscosity, as shown in Examples 14 and 15. Higher levels of acrylic acid monomers tend to increase viscosity, as shown in Example 16.
[0114] Preferably, the viscosity level should be low to facilitate the flow of the colorant through the colorant dispenser. The inventors of the present invention have found from the examples that the viscosity of the polymer additive of the present invention is proportional to the Tg (calculated by the Flory Fox equation) and is also proportional to the molecular weight (Mw). The viscosity is also proportional to the acidic functional groups (-COOH functional groups). Therefore, a lower molecular weight will reduce the viscosity; a lower acid level will reduce the viscosity; and a lower Tg will also reduce the viscosity.
[0115] Additionally, polymer additives polymerized primarily from acrylate monomers, or from substantially all or all acrylate monomers, have lower Tg than polymer additives polymerized from a combination of methacrylate and acrylate monomers. Without being bound by any particular theory, it is believed that methacrylate monomers form more rigid polymers due to restricted rotation, and all / substantially all acrylate monomers are more fluid and form more flexible monomers.
[0116] Based on Examples 1-18, the chain transfer agent can be present at about 4 phr to about 20 phr, or about 6 phr to about 17 phr, or about 9 phr to about 15 phr, or about 5 phr to about 11 phr.
[0117] When the viscosity values are averaged at the same shear rate, the viscosity range of the polymer additive of the present invention is preferably about 1.0 Pa s to about 20 Pa s, or about 3.0 Pa s to about 16 Pa s, or about 5 Pa s to about 12 Pa s. When the viscosity values are averaged at various shear rates, the viscosity range is preferably about 14 Pa s to about 36 Pa s, and more preferably about 15 Pa s to about 20 Pa s. It should be noted that all viscosity measurements were performed on the samples of the present invention without water. The fluidity of the samples of the present invention was also observed from the samples of the present invention without water.
[0118] It is known that at least one acid monomer is typically polymerized with other monomers. In one embodiment, it is preferred to utilize acrylic acid monomers as the primary acid monomers, and more preferably as the sole acid monomers. Although, as discussed above, the solubility of methacrylic acid monomers in water is about 89 g / l, acrylic acid monomers are miscible with water, having a water solubility of about 1,000 g / l. Substituting acrylic acid monomers for methacrylic acid monomers or using only acrylic acid monomers makes the hydrophobic oligomer additive more dispersible in water and less viscous.
[0119] The inventors of the present invention have also attempted to utilize the hydrophobic oligomer additive of the present invention to produce a colorant composition for commercialization. The optimal range of the hydrophobic oligomer additive of the present invention is from about 3 wt % to about 8 wt %, preferably from about 3.5 wt % to about 7 wt %, and preferably from about 4 wt % to about 6 wt % or from about 3 wt % to about 5 wt %.
[0120] In another embodiment, the hydrophobic oligomer additive of the present invention is used in combination with a conventional hydrophilic moisturizer (such as polyethylene glycol or polypropylene glycol). The hydrophilic moisturizer is preferably added at a reduced level of about 1% by weight to about 3% by weight in the grinding stage of the dispersed color pigment, and the hydrophobic oligomer additive of the present invention is added in the letdown phase of the dispersed color pigment dilution and mixing with the additive of the present invention to prepare the colorant composition. In this embodiment, the addition range of the hydrophobic oligomer additive of the present invention is from about 0.1% by weight to 4% by weight, preferably from about 0.2% by weight to about 3% by weight, preferably from about 0.3% by weight to about 2% by weight.
[0121] As used herein, the weight percentage of the hydrophobic oligomeric additive of the present invention used in the colorant composition is calculated using the hydrophobic oligomeric additive of the present invention after polymerization (including solids, water and other liquids), as shown in, for example, Example 1, and the colorant composition also includes solids, water and other liquids.
[0122] The viscosity of Examples 13, 14 and 15 was tested using the zirconium bead test. In this test, thickener was added to these Examples to bring the viscosity to 80-95 Krebs units (KU). 70 grams of each of these Examples and 20 grams of (Zirconium oxide) ceramic grinding beads were added to a 100 ml plastic cup. The cup was placed on a mixer and mixed at 2,400 rpm for 10 minutes. The beads were filtered from the resin and thoroughly rinsed with deionized water and dried overnight under ambient conditions. The beads were then visually assessed to see if they were lumped or sticking together. Visual results showed that Examples 13, 14 and 15 of the present invention did not cause the zirconium beads to clump, indicating that their low viscosity would not cause the beads to stick, and that the hydrophobic oligomer additives of the present invention would not adhere to the surface of their storage units or pipes.
[0123] Although the exemplary embodiments of the present invention disclosed herein obviously achieve the above-mentioned purpose, it should be understood that those skilled in the art can design numerous modifications and other embodiments. Therefore, it should be understood that the appended claims are intended to cover all such modifications and embodiments, which will fall within the spirit and scope of the present invention.
Claims
1. A colorant composition for tinting a paint or dye composition, comprising a pigment and an additive, wherein the additive is polymerized from at least one acrylate monomer and a chain transfer agent, wherein the additive has a weight average molecular weight (Mw) of about 2,000 Daltons to about 5,000 Daltons, wherein the chain transfer agent comprises hydrogen-sulfur (HS) functional groups and is present in an amount of about 8 to about 20 parts per hundred monomer (phr), wherein the additive has a glass transition temperature ranging from about -50°C to about -10°C, Wherein the additive is hydrophobic.
2. The colorant composition of claim 1, wherein the additive comprises from about 3% to about 8% by weight of the colorant composition, and wherein in determining the weight percentages, the additive and the colorant composition include solids, water, and liquids.
3. The colorant composition of claim 2, wherein the additive comprises from about 3.5% to about 7% by weight of the colorant composition.
4. The colorant composition of claim 2, wherein the additive comprises from about 4.0 wt. % to about 6 wt. % of the colorant composition.
5. The colorant composition of claim 2, wherein the additive comprises from about 3% to about 5% by weight of the colorant composition.
6. The colorant composition of claim 1, further comprising a hydrophilic moisturizer, wherein the additive comprises from about 0.1% to about 4% by weight of the colorant composition, and wherein in determining the weight percentages, the additive and the colorant composition include solids, water, and liquids.
7. The colorant composition of claim 6, wherein the additive comprises from about 0.2% to about 3% by weight of the colorant composition.
8. The colorant composition of claim 7, wherein the additive comprises from about 0.3% to about 2.5% by weight of the colorant composition.
9. An additive for a paint or dye composition or for a colorant composition, said additive being polymerized from at least one acrylate monomer and a chain transfer agent, wherein the additive has a weight average molecular weight (Mw) of about 2,000 Daltons to about 5,000 Daltons, wherein the chain transfer agent comprises hydrogen-sulfur (HS) functional groups and is present in an amount of about 4 to about 20 parts per hundred monomer (phr), wherein the additive has a glass transition temperature ranging from about -50°C to about -10°C, wherein the additive is hydrophobic, and The additive has a viscosity of about 1.0 Pa·s to about 20 Pa·s when the viscosity values are averaged at the same shear rate, or about 14 Pa·s to about 36 Pa·s when the viscosity values are averaged at various shear rates.
10. The additive of claim 9, wherein the additive is polymerized from at least 95 weight percent of one or more acrylate monomers.
11. The additive of claim 9, wherein the additive is polymerized with acrylic monomers.
12. The additive of claim 9, wherein the at least one acrylate monomer is butyl acrylate (BA) or 2-ethylhexyl acrylate (2-EHA).
13. A colorant composition for tinting a paint or dye composition comprising a pigment and the additive of claim 9.
14. A colorant composition comprising a coloring pigment and the additive of claim 9, wherein the additive is added to the colorant composition in a range of about 3 wt % to about 8 wt %, preferably about 3.5 wt % to about 7 wt %, preferably about 4 wt % to about 6 wt %, preferably about 3 wt % to about 5 wt %, and Wherein in determining the weight percentage, the additive and the colorant composition include solids, water and liquids.
15. A colorant composition comprising a coloring pigment, a hydrophilic moisturizer and the additive of claim 9, wherein the additive is added to the colorant composition in a range of about 0.1 wt % to about 4 wt %, preferably about 0.2 wt % to about 3 wt %, preferably about 0.3 wt % to about 2.5 wt %, Wherein in determining the weight percentage, the additive and the colorant composition include solids, water and liquids.
16. The additive of claim 9, wherein the chain transfer agent is present at about 6 phr to about 17 phr, or about 9 phr to about 15 phr, or about 5 phr to about 11 phr.
17. The additive of claim 9, wherein the viscosity is from about 3.0 Pa·s to about 16 Pa·s, or from about 5 Pa·s to about 12 Pa·s when viscosity values are averaged at the same shear rate.
18. The additive of claim 9, wherein the viscosity is from about 15 Pa·s to about 20 Pa·s when the viscosity values are averaged at various shear rates.
Citation Information
Patent Citations
Chain-transfer agents for emulsion polymerization and polymer products produced therewith
US4593081A
Storage-stable acrylate-functional alkyd resin compositions
US7256226B2
Precursor colorant composition for latex paint
US7402627B2
Emulsion polymers having multimodal molecular weight distributions
US7642314B2
Copolymer surfactants
US7750074B2